PENGARUH LABA AKUNTANSI, ARUS KAS OPERASI, ARUS KAS INVESTASI, ARUS KAS PENDANAAN, DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM - Nursita, Meta (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
This study aimed to examine the impact of accounting profit, operating cash flows, investment cash flows, financing cash flows and company size to stock returns on manufacturing firms sector for consumption by the corporate listed and registered under the Indonesia Stock Exchange within 2014 - 2016. This study employed Purposive Sampling method with a total of 39 companies taken as the sample in the present study. Data analysis process followed the following steps; descriptive statistical test, multicollinearity test, model fit test, regression model feasibility test, and hypothesis test. Statistical method used is panel data regression analysis. The result showed that accounting profit had partially significant impact on stock return; operating cash flows no had significant impact on stocks return; investment cash flows, and financing cash flows had no significant impact on stock return and company size had significant impact on stocks return. in addition, simultaneously, the results showed that the four aspects examined had statistically significant impact on stock return.